Security and data protection in brain computer interface systems - Titova А. М. (НТУ "ДП", 2024)
Sensors that directly measure the electrical activity of the brain are the first component, non-invasive sensors that are attached to the scalp or invasive sensors that are implanted directly into the brain. Electroencephalography (EEG) electrodes, noninvasive sensors, measure electrical potentials generated by neural activity in the cerebral cortex through the scalp. However, invasive sensors such as microelectrode arrays or electrocorticographic (ECoG) electrodes directly measure electrical activity on the surface of the brain or in specific brain regions. Modern BCI signal amplifiers are extremely sensitive and have low intrinsic noise. They can also amplify brain signals thousands of times while preserving their basic functions.
Keywords: інтерфейс « мозок комп’ютера»; безпека інформаційних технологій; захист інформаційних технологій